2012
DOI: 10.1080/13657305.2012.678554
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Willingness to Pay for Aquaculture Fish Products vs. Wild-Caught Seafood – A Case Study in Hawaii

Abstract: & This study aims to investigate Hawaii consumers' willingness to pay for fish product attributes including farmed vs. wild-caught. Hawaii presents an interesting case study as per capita seafood consumption is around three times the national average and 75% of seafood products are imported either from the U.S. mainland or foreign sources. For this study, questionnaires were administered both in-person and online. Conjoint analysis of four different fish species (tuna, salmon, tilapia and moi pacific threadfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 15 publications
(27 reference statements)
4
60
0
Order By: Relevance
“…A key finding, discussed in several studies, was that consumers often lack knowledge regarding aquaculture species and farming practices (Ii et al, 1995;Honkanen and Olsen, 2008;Robertson et al, 2002;Vanhonacker et al, 2011;Verbeke et al, 2007), including Integrated Multitrophic Aquaculture (IMTA) (Barrington et al, 2010;Shuve et al, 2009). One study investigating consumers' willingness to pay for aquaculture species found that respondents would pay more for wild-caught fish (Davidson et al, 2012), but another found that consumers would pay a price premium for farmed fish should there be improvements to environmental impact (Whitmarsh and Wattage, 2006). The factors influencing consumers' negative attitudes can be split into three main areas of concern: safety, environment and regulations.…”
Section: Introductionmentioning
confidence: 98%
“…A key finding, discussed in several studies, was that consumers often lack knowledge regarding aquaculture species and farming practices (Ii et al, 1995;Honkanen and Olsen, 2008;Robertson et al, 2002;Vanhonacker et al, 2011;Verbeke et al, 2007), including Integrated Multitrophic Aquaculture (IMTA) (Barrington et al, 2010;Shuve et al, 2009). One study investigating consumers' willingness to pay for aquaculture species found that respondents would pay more for wild-caught fish (Davidson et al, 2012), but another found that consumers would pay a price premium for farmed fish should there be improvements to environmental impact (Whitmarsh and Wattage, 2006). The factors influencing consumers' negative attitudes can be split into three main areas of concern: safety, environment and regulations.…”
Section: Introductionmentioning
confidence: 98%
“…Referring to freshness or storage mode, this survey attempts to compare consumers' preference between fresh, which is never frozen, and previously frozen tuna [33][34][35]. Secondly, two types of product processes are considered: farm raised and wild-caught [34,35]. Therefore, this study will examine consumer preference for the attributes of farm-raised tuna and contribute to an understanding of the future development of tuna farms.…”
Section: Other Tuna Attributes: Storage Mode and Pricementioning
confidence: 99%
“…Product demand is affected by attributes that may include flavor/taste, freshness, size, or fish form. Referring to freshness or storage mode, this survey attempts to compare consumers' preference between fresh, which is never frozen, and previously frozen tuna [33][34][35]. Secondly, two types of product processes are considered: farm raised and wild-caught [34,35].…”
Section: Other Tuna Attributes: Storage Mode and Pricementioning
confidence: 99%
“…Previous research has shown that sociodemographic characteristics (gender, age, education level, income, place of residence) have a high influence on consumer preferences for wild-caught versus farmed fish. Davidson et al (2012) reported that Hawaiian consumers prefer wild to farmed fish. Claret et al (2014) concluded that consumers with a higher objective knowledge about fish and a higher level of education were more ready to agree with scientific evidence and consequently more likely to make better and reasoned fish choices.…”
Section: Introductionmentioning
confidence: 99%